Komposisi Jenis dan Populasi Burung Cendrawasih di Kampung Malagufuk Distrik Klayili Kabupaten Sorong Provinsi Papua Barat - MAYA PATTIWAEL; AMATUS TUROT (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
One of the animals that are easy to find is a bird. Based on data about the increase in the number of bird species, it can be ascertained that these animals can be found in every region in Indonesia, with diverse species and even species that are endemic to a certain area. West Papua is one of the regions in Indonesia which is rich in various species of birds, including Cendrawasih which can also be found in the Natural Forest of Malagufuk Village, Klayili District, Sorong Regency. Based on information from the surrounding community, several types of Cendrawasih are often seen in the natural forests of Malagufuk Village, but their diversity and population are not known with certainty. This study aims to determine the diversity of species and population of Cendrawasih birds in the natural forest of Malagufuk Village, Klayili District, Sorong Regency, West Papua. Thus, the results of this study are expected to be a source of data in the context of preserving and protecting the existing Cendrawasih species. Data collection on the species composition and population of Cendrawasih was carried out using the Line Transect method by making 10 observation lines with a line length of 500 m each and a distance between lines of 100 m. The results showed that there were found 3 spesies of Cendrawasih with estimated populations and densities as follows: Cendrawasih Kuning Kecil (Paradisaea minor) had an estimated population of 7.48 individuals with a density of 2.93 individuals / ha; Cendrawasih Raja (Cicinnurus regius) has an estimated population of 5 individuals with a density of 1.67 individuals / ha; and Toowa Cemerlang (Ptiloris magnificus) had an estimated population of 2.22 individuals with a density of 0.74 individuals / ha. When the research was carried out, it was seen that the three types of Cendrawasih used several types of trees as places for activities (playing or dancing), namely Matoa (Pometia coreacea), Merbau (Intsia bijuga), Damar (Agathis dammara). Beringin (Ficus benjamina), and Pala hutan (Myristica sp) with tree heights above 20 m.